Cerambycidae (Insecta, Coleoptera) from the Caatinga biome: checklist, new records and new species from Sergipe state (Brazil) - de L. Nascimento, Francisco E.; Rodrigues de Sousa, Mayre Ellen [UNESP]; Bravo, Freddy (Taylor & Francis, 2021)
Based on recently collected material and specialised catalogues, we list 52 species of Cerambycidae occurring in the state of Sergipe, Brazil. A total of 25 specimens of Cerambycidae were collected in Propriá municipality, supported by the Semiarid Biodiversity Research Programme (PPBio /Semiarido). Fifteen species were identified in 14 genera, 10 tribes and two subfamilies. Eight species are new records for Sergipe. A new species of the genus Oreodera Audinet-Serville (Lamiinae, Acrocinini) is described and illustrated. Additionally, we describe the morphology of the male genitalia of Oreodera exigua Monné & Fragoso, 1988. The number of species known from Sergipe increases from 42 to 52 species. http://www.zoobank.org/urn:lsid:zoobank.org:pub:0229C1C6-9B5B-4618-9398-D3C8E94497E4.
Keywords: Acrocinini; Brazilian semiarid; Chrysomeloidea; morphology; taxonomy